Rein tension used by riders during regular riding sessions - Egenvall, A.; Roepstorff, L.; Rhodin, M.; Eisersiö, M. (DCA Report; Nr. 044, 2014)
Though several studies have investigated rein tension during riding there is information deficit of rein tension relative to gaits and exercises, as well as of between-rider and between-horse effects. The aim of this study was to examine the rein tension employed by professional riders, riding horses in their own training during regular and preferred riding sessions. Eight professional riders each rode 3 horses in their own training, asked to demonstrate their normal routine for dressage, each rider determining the session lengths. Training session were video recorded (25Hz). The horses were fitted with a custom-developed rein tension meter (128Hz), measuring range 0-50oN, where data acquisition was made through an inertial measurement unit (IMU) fastened on the horse`s browband. Gaits and exercises were classified from the video by one observer and validated from the IMU acceleration signal. The rein tension was determined at walk, trot, left and right canter for each rein. Reins were defined as dominant versus non-dominant. `Dominant` was the right rein in right handed riders and the left rein in one left-handed rider. Mixed models analysis was used to study data on short reins, median 1) dominant and 2) non-dominant log-transformed rein tension, including gait (walk, trot, left canter and right canter) and whether horses worked straight or bent (corners, circles, halfpass, shoulder-in), including the 2-way interaction. `Horses within rider` was a random effect. The mean duration of the riding sessions was 32 (STD 6) min. Of the time 69% was on short reins. In total, 36% of the time was in walk, 35% in trot and 20% in canter (51%/49% left/right canter). Median rein tension in walk was 9N/7N for the dominant/non-dominant rein, in trot 14N /14N, in left canter 19N/ 20N and right canter 20N/19N. The gait and exercise interactions were significant (P<0.0001). In total, 39 of 67 pair-wise comparisons were significant for the dominant rein, and 29 of 67 for the non-dominant rein. Ignoring comparisons between gaits, we note there were no significant differences between different exercises within trot, while there were 4 significant differences between exercises within canter (P<0.03, left and right canter compared as one gait) and 4 within walk (P<0.0001). For walk, the right bend had the highest median rein tension for both reins (P<0.0001 compared to left bend and straight). For both models the variation introduced by horses within riders was 65%. LP: Rein tension differences were found between gaits and riders, but we also found differences between exercises within gait. Awareness of this may increase the understanding of how to use the rein from both a welfare point of view and for achieving a successful sport horse.